A review of the potential therapeutic role of statins in the treatment of Alzheimer’s disease: current research and opinion - Sánchez-Ferro, Álvaro (Dove Medical Press, 2013)
Alzheimer’s disease is one of the most prevalent neurodegenerative disorders. However, there is no current treatment, which definitively influences disease progression over a sustained period. Numerous studies linking an increase in serum cholesterol, mainly during midlife, with the pathogenic process of Alzheimer’s disease have been published. Therefore, the role of statins as a therapy in this disorder may be of great interest. The aim of the present review is to summarize of the role of statins in the treatment of Alzheimer’s disease.